Backgrounds of sustainable development formation of civil society - Михайленко, Дар’я Геннадіївна (Technology audit and production reserves, 2015)
The backgrounds of sustainable development formation of civil society are considered in this article. It is updated a list of regulatory documents according to which is necessary to focus in solving the problems of sustainable development of civil society in Ukraine. The aim of the study is to analyze the current conditions of the sustainable development formation of civil society and determine its paths of development. Using a combination of methods of scientific knowledge has allowed to analyze the current trends and the state of non-governmental organizations in Ukraine. Analysis of the state of non-governmental organizations showed that there is a stable dynamics of their development, but this is a formality. Most of the population is insufficiently informed about their activities. The challenges are identified and priorities of social policy with the promotion of civil society institutions, preservation and coordination of interests and rights of citizens are specified. The proposed guidelines can be used to understand the processes of formation, development and functioning of civil society institutions.